2019
DOI: 10.1186/s12934-019-1053-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of scFv protein recovery from E. coli by in vitro refolding and mild solubilization process

Abstract: BackgroundThe production of therapeutically active single chain variable fragment (scFv) antibody is still challenging in E. coli due to the aggregation propensity of recombinant protein into inclusion bodies (IBs). However, recent advancement of biotechnology has shown substantial recovery of bioactive protein from such insoluble IBs by solubilization and refolding processes. In addition, gene fusion technology has also widely been used to improve the soluble protein production using E. coli. This study demon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
33
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(37 citation statements)
references
References 45 publications
4
33
0
Order By: Relevance
“…We have shown that the maximum intracellular IB size varied between 500 and 700 nm [16], which resembles a ratio around 30% of IB per cell given the rough E. coli size estimation of 2 µm. Furthermore, the basic and cheap refolding with glycerol as single additive in deionized water resulted in a refolding yield of around 30% compared to ~ 49% [39] or 32.3% [35] for similar proteins in more complex buffers.…”
Section: Discussionmentioning
confidence: 99%
“…We have shown that the maximum intracellular IB size varied between 500 and 700 nm [16], which resembles a ratio around 30% of IB per cell given the rough E. coli size estimation of 2 µm. Furthermore, the basic and cheap refolding with glycerol as single additive in deionized water resulted in a refolding yield of around 30% compared to ~ 49% [39] or 32.3% [35] for similar proteins in more complex buffers.…”
Section: Discussionmentioning
confidence: 99%
“…The resulting pellet protein was washed 4 to 5 times with TE 50/20 (50 mM Tris pH 8.0 and 20 mM EDTA 20) buffer to remove impurities and extra salts. The remaining pellet was re-solubilised using mild denaturing agent such as 4.0 M urea and 5% n-propanol along with PBS buffer (pH 8.1) (Sarker et al 2019) and was centrifuged at 20,000 rpm for 10 min. The soluble protein fraction was initially purified by using Ni-NTA agarose beads and was confirmed by western blot using anti-His antibody.…”
Section: Solubilisation and Purification Of Fubc Proteinmentioning
confidence: 99%
“…Chaperone-assisted folding system did not help remarkably to express the Fubc recombinant protein in the soluble form. Therefore, the insoluble pellet fraction of Fubc protein was further utilised in mild solubilisation process (Sarker et al 2019) to recover soluble Fubc protein. Initially, the recovered soluble Fubc protein fraction was purified by using Ni-NTA agarose beads, and the purified protein band was confirmed by Western blot analysis using anti-His tag monoclonal antibody (Fig.…”
Section: Expression and Purification Of Recombinant Fubc Proteinmentioning
confidence: 99%
“…Batch mode refolding of solubilized IBs can be carried out using rapid or pulse dilution, by diafiltration and dialysis or by on-column chromatographic methods. In a recent study, it was also established that mild solubilization can be considered in terms of cost, time, and tag-free nature for the recovery of scFv from IBs (Sarker et al, 2019). The various methods used for refolding to recovery biologically active proteins have been reviewed previously (Rathore et al, 2013;Yamaguchi and Miyazaki, 2014).…”
Section: Downstream Process Developmentmentioning
confidence: 99%